Antibody titre against 3 doses of hepatitis B vaccine among preterm and term babies - Mollah, AH; Naher, N; Rahman, S; Chowdhury, AM (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2012 Jan;21(1):109-113 The abstract of this article is available on the PubMed website